Analisis Diklat Teknis Fungsional dalam Rangka Pengembangan Kualitas Pegawai pada Badan Penanggulangan Bencana Daerah (BPBD) Kota Semarang - Kesuma, Gilang Agitya; Yuniningsih, Tri; Rihandoyo, Rihandoyo (Journal of Public Policy and Management Review, 2014)
This study aims to analysis of functional technical education and training in order of employee quality development in the area of disaster management agency of Semarang city. This research used method descriptive qualitative. This subjects in this study consist of 6 (six) main informant. Based on the research result show employees quality of the disaster management agency of Semarang city can be categorized good. Either even though there is still some dimension assessed less well. While employee development on the disaster management agency of Semarang city categorized less well, because some employee quality development programs in strategic plan of disaster management agency of Semarang city 2011 – 2015 not yet implemented that is MFR (Medical First Responder) and Scuba Diving. Conclusions in this study was the overall performance of the disaster management agency of Semarang city was good, while for employee quality development assessed not good. Based on the conclusions researchers to a disaster management agency of Semarang city to correct employee quality aspect and implemented employee quality development in Renstra of disaster management agency of Semarang city 2011 – 2015 so that quality and the ability of employees increased.